OPPORTUNITIES OF ARTPEDAGOGY IN THE DEVELOPMENT OF CREATIVE SKILLS OF FUTURE MUSIC EDUCATION TEACHERS (Scientific journal of the Fergana State University, 2023)
This article is devoted to the ways of developing creativity and thinking of future music teachers through artpedagogy, which is a modern form of education recognized as a part of the field of pedagogy. It is also supposed to describe the methodological approaches to the formation of the professional readiness of students with a high level of knowledge in the field of art to see the systematized results of creative activity.